First step you should do is s<span>implify both sides of your equation:
</span>29-(x+8)=6x-7
Distribute the Negative Sign:
29+-1(x+8)=6x-7
29+-1x+(-1)(8)=6x-7
29+-x+-8=6x-7
29+-x+-8=6x+-7
<span>Combine Like Terms:
</span>(-x)+(29+-8)=6x-7
-x+21=6x-7
<span>Subtract 6x from both sides:
</span>-x+21-6x=6x-7-6x
-7x+21=-7
<span>Subtract 21 from both sides:
</span>-7x+21-21=-7-21
-7x=-28
<span>Divide both sides by -7:
</span>-7x/-7 = -28/-7
And now your answer should be:
x=4
~~~~~
Good luck~ Sans
Answer:
because it will bounce high and hit something.
Step-by-step explanation:
Answer:
right 2 , up 3.
Step-by-step explanation:
The -2 moves 2 to the right and the + 3 means 3 up.
Answer:
Since g(x) = f(2x), this means we substitute 2x in place of x for f(x):
g(x) = f(2x) = (2x)² = 4x²
Graphing this, the parabola is not moved from the parent graph f(x) = x², but the graph is compressed horizontally by a factor of 4.Step-by-step explanation:
A 1:12 is the answer for this question